Guidelines for the preventive health care of hairdressing apprentices - Aleksandra Golińska-Zach; Marta Wiszniewska; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2017)
Hairdressing is one of the most developing branch of the service industry in Poland. Providing representatives of this occupational group with preventive health care services it should be remembered that they are at risk of skin and respiratory diseases, which occur due to a quite frequent exposure to harmful agents in the work environment of hairdressers and hairdressing apprentices. Interestingly, a much lower number of researches concentrate on respiratory symptoms than on skin disorders in hairdressers. The authors of this article have carried out the first Polish follow-up study focused not only on skin disorders but also on respiratory tract symptoms in hairdressing apprentices. The results of the study have been reported in other publications while this paper presents a literature review based on EBSCO and PubMed databases, Elsevier and contained articles (on the subject discussed in this paper). On the basis of information obtained from the authors' own research evidence and from the literature review, the guidelines for the preventive health care of hairdressing apprentices were developed. It was confirmed that neither determination of allergen-specific immunoglobulin E (IgE) nor performance of skin prick tests (SPTs) and patch tests for hairdressing factors are necessary. They should be performed as a part of preventive medical examination only in those apprentice candidates and trainees in this profession who report work-related symptoms and it is suspected that they result from exposure to particular factor in the work environment. Med Pr 2017;68(5):677-687